Work stress and risk factors in the nursing profession at two hospitals in Kuantan - Fatin Najihah Mislin; Nor Ashikin Sopian; Nurliyana Moh Hussin; Nurul Ainun Hamzah; Wan Zaiton Wan Sulaiman (Current Science and Technology, 2026)
This study aims to determine the risk factors that influence work stress among nurses at two hospitals in Kuantan, Pahang, using a validated questionnaire. The findings of this research would serve as a guideline to propose a better strategy to help nurses cope with stress at the workplace. A cross-sectional study was conducted at the hospitals to examine work stress and its associated risk factors among nurses, using a convenience sampling method. Data collection involved distributing questionnaires consisting of socio-demographics, the risk factors of work stress, and work stress. The results indicate that shift work is perceived as the primary risk factor for occupational stress among nurses, with the highest mean score (4.09), followed by workload (3.75) and the work environment (3.23). Correlation analysis shows that only the relationship between shift work and work environment is statistically significant (r = -0.411, p < 0.01), indicating that higher shift demands correlate with a low perception of the environment. On the other hand, workload (r = -0.208), work environment (r = 0.206), and shift work (r = 0.123) show non-significant, low correlations with perceived work stress in this study. This study recommends that hospital management take proactive steps to address the stress issues that currently exist by offering a variety of suitable supports that would include techniques of handling stress at work.